Synthesis of High-Crystallinity DPP Polymers with Balanced Electron and Hole Mobility - Di Pietro, Riccardo; Erdmann, Tim; Carpenter, Joshua H.; Wang, Naixiang; Shivhare, Rishi Ramdas; Formanek, Petr; Heintze, Cornelia; Voit, Brigitte; Neher, Dieter; Ade, Harald; Kiriy, Anton (Chemistry of Materials, 2017)
We review the Stille coupling synthesis of P(DPP2OD-T) (Poly[[2,5-di(2-octyldodecyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione-3,6-diyl]-alt-[2,2′:5′,2″-terthiophene-5,5″-diyl]]) and show that high-quality, high molecular weight polymer chains are already obtained after as little as 15 min of reaction time. The results of UV-vis spectroscopy, grazing incidence wide-angle X-ray scattering (GIWAXS), and atomic force microscopy show that longer reaction times are unnecessary and do not produce any improvement in film quality. We achieve the best charge transport properties with polymer batches obtained from short reaction times and demonstrate that the catalyst washing step is responsible for the introduction of charge-trapping sites for both holes and electrons. These trap sites decrease the charge injection efficiency, strongly reducing the measured currents. The careful tuning of the synthesis allows us to reduce the reaction time by more than 100 times, achieving a more environmentally friendly, less costly process that leads to high and balanced hole and electron transport, the latter being the best reported for an isotropic, spin-coated DPP polymer.
CRIS-Team Scopus Importer:2022-04-14